2016
DOI: 10.1111/jan.13027
|View full text |Cite
|
Sign up to set email alerts
|

Forced air warming to maintain normoTHERMIa during SEDation in the cardiac catheterization laboratory: protocol for the THERMISED pilot randomized controlled trial

Abstract: ACTRN12616000013460.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This analysis was undertaken from the perspective of the organisation responsible for deciding which resources to use for thermal comfort during procedures in their cardiac catheterisation laboratory. Detailed descriptions of the trial have been reported in Conway et al (2017) and Conway and Duff (2016).…”
Section: Designmentioning
confidence: 99%
“…This analysis was undertaken from the perspective of the organisation responsible for deciding which resources to use for thermal comfort during procedures in their cardiac catheterisation laboratory. Detailed descriptions of the trial have been reported in Conway et al (2017) and Conway and Duff (2016).…”
Section: Designmentioning
confidence: 99%
“…A randomised controlled trial was conducted to compare FAW with passive warming using heated cotton blankets during elective procedures performed under sedation in a CCL. Full details of the protocol for this study have been published, 13 and it was prospectively registered (ACTRN12616000013460). Informed consent was obtained from each participant, and the study protocol conforms to the 1975 Declaration of Helsinki as reflected by the university and hospital human research ethics committee approvals (UCH HREC 1505; QUT HREC 1500000643; SVH HREC 15/263).…”
Section: Methodsmentioning
confidence: 99%
“…Without active heating, the core temperature can potentially decrease by 1 to 1.5°C in the first hour after induction of anaesthesia (Conway & Duff 2016). Perioperative hypothermia occurs due to interference with the regulation of normal temperature by anaesthetic drugs, the reception of large volumes of intravenous and irrigation fluids and exposure of the skin for prolonged periods (Campbell et al 2015).…”
Section: Introductionmentioning
confidence: 99%